Effectiveness of vardenafil versus papaverine in penile Doppler ultrasonography - Ardicoglu, A; Kocakoc, E; Tuygun, UO; Bozgeyik, Z; Orhan, I (Karger, 2005)
Purpose: To evaluate erectile dysfunction, penile color Doppler ultrasound is currently considered the best method. But intracavernous injection is invasive and has adverse effects, such as prolonged erection and risk of priapism. In our study we want to evaluate whether vardenafil can be used instead of papaverine in penile Doppler ultrasonography. Materials and Methods: A total of 24 patients with erectile dysfunction underwent color Doppler ultrasound before and after intracavernous injection of 60 mg papaverine with genital and audiovisual sexual stimulation. Peak flow and end diastolic velocity were measured in the recorded waveforms obtained 0, 1, 5, 10 and 20 min after injection. The patients also underwent color Doppler ultrasound after a 10-mg oral dose of vardenafil with genital and audiovisual sexual stimulation and at least 5 days after the prior examination. The same parameters were measured at 30, 45, 60, 75 and 90 min after the drug administration. We compared the results with the values obtained after papaverine injection. Results: After oral vardenafil mean peak flow velocity significantly increased starting at 30 min and achieving a maximum value at 60 min. There were no significant differences in the 2 methods in mean peak velocity 1, 5, 10 and 20 min after papaverine injection, and 30, 45, 60, 75 and 90 min after oral vardenafil administration. Although papaverine injection is the gold standard for penile color Doppler ultrasound, it has severe adverse effects such as prolonged erection which we observed in 3 patients (12,5%) and required pharmacological detumescence. After vardenafil no severe adverse effects were observed. Conclusions: Vardenafil administration achieved increased peak flow velocity comparable to that after intracavernous papaverine injection. With no prolonged erection vardenafil is a safer alternative compared to more invasive intracavernous injection and is also an alternative for patients who fear injections. Copyright (c) 2005 S. Karger AG, Basel.
Keywords: vardenafil; papaverine; impotence; ultrasonography; color Doppler; penis